Two isocitrate dehydrogenases from a plant pathogen Xanthomonas campestris pv. campestris 8004. Bioinformatic analysis, enzymatic characterization, and implication in virulence. (10th June 2016) - Lv, Changqi; Wang, Peng; Wang, Wencai; Su, Ruirui; Ge, Yadong; Zhu, Youming; Zhu, Guoping
Abstract : Isocitrate dehydrogenase (IDH) is a key enzyme in the tricarboxylate (TCA) cycle, which may play an important role in the virulence of pathogenic bacteria. Here, two structurally different IDHs from a plant pathogen Xanthomonas campestris pv. campestris 8004 (XccIDH1 and XccIDH2) were characterized in detail. The recombinant XccIDH1 forms homodimer in solution, while the recombinant XccIDH2 is a typical monomer. Phylogenetic analysis showed that XccIDH1 belongs to the type I IDH subfamily and XccIDH2 groups into the monomeric IDH clade. Kinetic characterization demonstrated that XccIDH1's specificity towards NAD + was 110‐fold greater than NADP +, while XccIDH2's specificity towards NADP + was 353‐fold greater than NAD + . The putative coenzyme discriminating amino acids (Asp268, Ile269 and Ala275 for XccIDH1, and Lys589, His590 and Arg601 for XccIDH2) were studied by site‐directed mutagenesis. The coenzyme specificities of the two mutants, mXccIDH1 and mXccIDH2, were completely reversed from NAD + to NADP +, and NADP + to NAD +, respectively. Furthermore, Ser80 of XccIDH1, and Lys256 and Tyr421 of XccIDH2, were the determinants for the substrate binding. The detailed biochemical properties, such as optimal pH and temperature, thermostability, and metal ion effects, of XccIDH1 and XccIDH2 were further investigated. The possibility of taking the two IDHs into consideration as the targets for drug development to control the plant diseases caused by Xcc 8004 were described and discussed thoroughly.